IMPLEMENTASI CAESAR CIPHER PADA ALGORITMA KRIPTOGRAFI KLASIK DALAM PENYANDIAN PESAN - Ziliwu, Krisma Budi; Maslan, Andi; Kremer, Hendri (Computer Science and Industrial Engineering, 2022)
Criptography is an art of knowledge to learn of securing the information in a message. The security of the message consists of confidentiality, integrity and authentication. The key for coding the message to convert the original message into readable form has different algorithms. The difference of algorithm based of what the key used when encript and descrypt the message. Symmetric key cryptography uses same key when user do encrypt and descrypt. But when user do encrypt and descrypt with different key it’s called asymmetric key cryptography. The main topic of this paper will be concerned about how to do symmetric key algorithm with subtitution method. Caesar cipher is example of subtitution method.